2009
DOI: 10.1080/08958370802474736
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Respiratory Tract Lining Fluid Ascorbate Concentrations Through Supplementation with Vitamin C

Abstract: Low molecular weight antioxidants within human respiratory tract lining fluids (RTLFs) have been proposed to confer protection against the damaging action of inhaled oxidant gases. There is therefore considerable interest in augmenting the concentrations of these moieties at the airlung interface to protect against injury to the airway epithelium, the induction of inflammation, and declines in lung function. To determine whether RTLF ascorbate concentrations could be augmented through vitamin C supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
(62 reference statements)
1
13
0
Order By: Relevance
“…When [1,[3][4][5][6][7][8][9][10][11][12][13][14][15] N 2 ] urate-spiked plasma samples were subjected to the alkaline SPE procedure, we found that the corrected ion ratio increased nonlinearly with the concentration of spiked [1,[3][4][5][6][7][8][9][10][11][12][13][14][15] N 2 ] urate (Fig. 2).…”
Section: Assessment Of Artifactual Conversion Of Urate To Allantoin Imentioning
confidence: 92%
See 3 more Smart Citations
“…When [1,[3][4][5][6][7][8][9][10][11][12][13][14][15] N 2 ] urate-spiked plasma samples were subjected to the alkaline SPE procedure, we found that the corrected ion ratio increased nonlinearly with the concentration of spiked [1,[3][4][5][6][7][8][9][10][11][12][13][14][15] N 2 ] urate (Fig. 2).…”
Section: Assessment Of Artifactual Conversion Of Urate To Allantoin Imentioning
confidence: 92%
“…When plasma was spiked with high, but physiologically relevant levels of [1,3-15 N 2 ] urate (equivalent to 400 mM plasma urate), the corrected 400-398 m=z ion ratio was *1.3. This indicates that under these conditions, the amount of 15 N-labelled allantoin produced by artifactual conversion of [1,[3][4][5][6][7][8][9][10][11][12][13][14][15] (Fig. 2).…”
Section: Assessment Of Artifactual Conversion Of Urate To Allantoin Imentioning
confidence: 98%
See 2 more Smart Citations
“…44,45 Furthermore, acute vitamin C supplementation (1 g) is associated with a rapid, but transient, rise in vitamin C concentrations in respiratory tract lining fluids, which could provide immediate antioxidant protection to lung tissues and temporarily attenuate oxidative stress in airways. 46 In elderly patients hospitalized with acute respiratory infections, patients randomized to receive 200 mg of vitamin C daily recovered more rapidly than patients receiving placebo, and the vitamin C supplemented patients experienced lower death rates compared with the placebo group (4% vs 17%). 47 In a Japanese population (439 patients with atrophic gastritis), chronic vitamin C supplementation (500 mg/d) reduced the number of common colds by 20% over a 3-year period compared with placebo ingestion.…”
Section: The Common Coldmentioning
confidence: 99%